Influence of Velocity on Hydrodynamic Flow Characteristics around Subsea Pipelines: A Numerical Analysis - Luh Putri Adnyani; Samsu Dlukha Nurcholik; Destyariani Liana Putri (International Journal of Marine Engineering Innovation and Research, 2025)
This study investigates the influence of flow velocity on hydrodynamic flow characteristics around free-span subsea pipelines using computational fluid dynamics (CFD). Simulations were conducted at flow velocities of 1.1 m/s, 2.5 m/s, and 3.0 m/s to examine changes in mean flow field, bed shear stress, pressure distribution, and wake development. Results show that increasing velocity transitions the wake from stable laminar to turbulent with fully developed vortex streets, intensifying vortex shedding, wake asymmetry, and unsteady forces. Higher velocities significantly amplify peak bed shear stress, adverse pressure gradients, and the depth of velocity deficits, leading to prolonged wake recovery and increased turbulence. These effects have critical implications for vortex-induced vibration (VIV), hydrodynamic loading, and scour potential, emphasizing the need to consider velocity variation in the design and integrity assessment of subsea pipelines.